Platform governance and social justice : governing hate speech on social media - Otero, Paloma Viejo (Digital activism and society: politics, economy and culture in network communication, 2024)
Platform Governance and Social Justice outlines principles and mechanisms social media platforms have adopted to govern hate speech, exploring how a social justice approach to hate speech regulation would effectively reduce the circulation of harmful content targeting historically oppressed groups. Focusing on the two interrelated topics of hate speech and platform governance, Paloma Viejo Otero pursues how platform governance (policies, regulation, moderation) are supported by different ideals and approaches to hate speech. Identifying four traditional approaches that have underpinned hate speech regulation in the contemporary digital landscape, Otero proposes a fifth approach called the Social Justice Approach (SJA), an original contribution to the field of research. Combining interviews with CEOs of platforms that are guided by policies, compared to conventional commercial platforms such as Facebook, and interviews with users/participants on these platforms, SJA is presented as a possible alternative to the dominant policy position of platform governance. Could an SJA approach possibly reduce the circulation of harmful content directed at marginalised and oppressed groups and subjects? Otero answers this question and more as social media's influence and popularity continues to grow.